2013
DOI: 10.1007/s13224-013-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Peripartum Hysterectomy in a Tertiary Care Hospital in Saudi Arabia

Abstract: Hysterectomy for the control of obstetric hemorrhage is usually associated with significant mortality and morbidity. Prompt intervention to include peripartum hysterectomy may likely decrease the rate of maternal deaths and significant maternal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
20
1
1
Order By: Relevance
“…15 Re-exploration was performed in 11 cases (8.9%). This rate is lower than reported by Begum et al 28 which was 15%. DIC was the major contributing factor that stimulates the re-exploration.…”
Section: Discussioncontrasting
confidence: 68%
“…15 Re-exploration was performed in 11 cases (8.9%). This rate is lower than reported by Begum et al 28 which was 15%. DIC was the major contributing factor that stimulates the re-exploration.…”
Section: Discussioncontrasting
confidence: 68%
“…1,6,17,19,20,[23][24][25][26][27][28][29]31,33,34,37,38,40,41,43,[45][46][47][48][49][50][51][52][53]57,58,60,62,64,72,78,83,86,87,93,94,96,[105][106][107][108][109]112,114,[118][119][120][121]…”
Section: Inclusion Is Summarized Inmentioning
confidence: 99%
“…57,65,80,90 Five case-control studies reported multivariate analysis. 87,110 All but three studies 88,89,118 mentioned prevalence of emergency peripartum hysterectomy; four were excluded from prevalence estimation, because these reported only cesarean 21,71,79 or postpartum 136 hysterectomies. Two mentioned analysis of confounding but no multivariate analysis.…”
Section: Inclusion Is Summarized Inmentioning
confidence: 99%
See 1 more Smart Citation
“…All were identified as independent risk factors for uterine atony [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Indicationsmentioning
confidence: 99%